Association of the Diabetes Health Plan with emergency room and inpatient hospital utilization: a Natural Experiment for Translation in Diabetes (NEXT-D) Study. Issue 1 (11th January 2021) - Moin, Tannaz; Steers, Neil; Ettner, Susan L; Duru, Kenrik; Turk, Norman; Chan, Charles; Keckhafer, Abigail M; Luchs, Robert H; Ho, Sam; Mangione, Carol M
Abstract : Introduction: To examine the association of a novel disease-specific health plan, known as the Diabetes Health Plan (DHP), with emergency room (ER) and hospital utilization among patients with diabetes and pre-diabetes. Research design and methods: Quasi-experimental design, with employer group as the unit of analysis, comparing changes in any ER and inpatient hospital utilization over a 3-year period. Inverse probability weighting was used to control for differences between employers purchasing DHP versus standard plans. Estimated differences in utilization are calculated as average treatment effects on the treated. We used employees and dependents from employer groups contracting with a large, national private insurer between 2009 and 2012. Eligibility and claims data from continuously covered employees and dependents with diabetes and pre-diabetes (n=74 058) were aggregated to the employer level. The analysis included 9 DHP employers (n=7004) and 183 control employers (n=67 054). Results: DHP purchase was associated with 2.4 and 1.8 percentage points absolute reduction in mean rates of any ER utilization, representing 13% and 10% relative reductions at 1 and 2 years post-DHP (p=0.012 and p=0.046, respectively). There was no significant association between DHP purchase and hospital utilization. Conclusion: Employers purchasing diabetes-specific health benefit designs may experience lower rates of resource-intensive services such as ER utilization.